Immigrants and narrative: The role of the church - Klaasen, John (Stellenbosch Theological Journal, 2024)
Since 1960 immigration has been mainly intra-continental on the African continent. With more countries achieving independence and the decline of colonization, there has been a significant decrease of intra-continental migration. Compared to the rest of the continent, South Africa has a relatively low emigration rate. The rate of people emigrating to European countries from Africa is higher than those who emigrate within the African continent. The narrative church provides the space for migrants to exercise their agency. Challenging distorted and false identities is one way of exercising agency. Narrative church welcomes migrants as the Other that form identity of both those who participate in the Christian narrative and those who are connected with the narrative through distant ways such as dialogue, virtual or intellectual and practical engagements.